Effect of propolis on postharvest control of anthracnose and quality parameters of 'Kent'mango - Mattiuz, Ben-Hur [UNESP]; Ducamp-Collin, Marie-Noelle; Machado Mattiuz, Claudia Fabrino; Vigneault, Clement; Marques, Kelly Magalhaes [UNESP]; Sagoua, Woeheoudama; Montet, Didier (Elsevier B.V., 2015)
The objective of this study was to evaluate the efficacy of propolis treatment for reducing anthracnose development on mango fruit of variety Kent; and compare its efficacy to chitosan treatment, which is already a well-studied natural produce. For in vitro experiments, Petri plates were amended with (0, 0.5, 1.0, 1.5, 2.0 and 2.5% v/v) propolis or (0, 0.25, 0.5, 1.0, 1.5 and 2.0% w/v) chitosan solutions. For the in vivo experiments, mangoes were infected with a spore suspension of Colletotrichum gloeosporioides and solution of either propolis (1.5%) or chitosan (1.5%) were used for controlling the pathogen development. The fruits were stored for 14 days at 12 +/- 1 degrees C and 83 +/- 2% RH, and then, for another 7 days at 23 degrees C, 82%. Lesion area, firmness, chemical composition, as well as color of the skin were used for evaluating and compare the performance of the two products. Even if the in vitro results demonstrated the net superiority of propolis for controlling the development of the pathogen, the in vitro results showed the opposite order when classifying the performance of the products with alive fresh produce. The results obtained suggested that propolis, as well as chitosan, may be used as treatment for controlling anthracnose, maintaining quality, and increasing the shelf life in 'Kent'mango. However, propolis was far from producing competitive results to chitosan treatment performance. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Mangifera indica; Chitosan; Postharvest; Natural product